VVV-WIT-01: highly obscured classical nova or protostellar collision?. Issue 4 (20th January 2020) - Lucas, P W; Minniti, D; Kamble, A; Kaplan, D L; Cross, N; Dekany, I; Ivanov, V D; Kurtev, R; Saito, R K; Smith, L C; Catelan, M; Masetti, N; et al.
ABSTRACT: A search of the first Data Release of the VISTA Variables in the Via Lactea (VVV) Survey discovered the exceptionally red transient VVV-WIT-01 ( H − Ks  = 5.2). It peaked before March 2010, then faded by ∼9.5 mag over the following 2 yr. The 1.6–22  μ m spectral energy distribution in March 2010 was well fit by a highly obscured blackbody with T ∼ 1000 K and $A_{K_s} \sim 6.6$  mag. The source is projected against the Infrared Dark Cloud (IRDC) SDC G331.062−0.294. The chance projection probability is small for any single event ( p ≈ 0.01–0.02), which suggests a physical association, e.g. a collision between low mass protostars. However, blackbody emission at T ∼ 1000 K is common in classical novae (especially CO novae) at the infrared peak in the light curve due to condensation of dust ∼30–60 d after the explosion. Radio follow-up with the Australia Telescope Compact Array detected a fading continuum source with properties consistent with a classical nova but probably inconsistent with colliding protostars. Considering all VVV transients that could have been projected against a catalogued IRDC raises the probability of a chance association to p  = 0.13–0.24. After weighing several options, it appears likely that VVV-WIT-01 was a classical nova event located behind an IRDC.